Prospects for producing liquid wood-based biofuels and impacts in the wood using sectors in Europe. (January 2018) - Kallio, A. Maarit I.; Chudy, Rafal; Solberg, Birger
Abstract: Rapid decarbonisation of the transport sector calls for increased use of biofuels. Part of the increase may be covered by fuels produced from logging residues, wood chips and round wood. This article addresses the economic potential and possible impacts of increased production of such wood based biofuels on the forest industries and production of wood based heat and power in the European Economic Area. A global model for the markets and trade of forest biomass and products, the EFI-GTM was applied for the analysis. The results indicate, firstly, that policy choices will have strong impacts on the allocation of biomass use between heat and power production and the production of liquid biofuels. Hence, the policy makers must have very clear goal setting for the preferred ways to solve the shift from the fossil fuel based energy system to a less carbon intensive one. Nevertheless, because large investments in biofuel production take time to plan and construct, and because the annual forest growth exceeds the harvests of wood in various parts of Europe, there is time to adjust the policies to control the market development. Secondly, even assuming the goal of limiting the global warming to 2 °C, the European forest industry production is projected to be rather little affected by the increased competition for biomass with the energy sector. This is because the rivalling regions are facing similar biomass demand challenges. Also, the relatively abundant wood biomass resources in Europe help the European forest industry to maintain its market shares. Highlights: Wood biomass allocation between heat and power production and biofuels is extremely sensitive to policies chosen. There is time to adjust the policies to control the development of the use of wood for energy in Europe. Using biomass as one of the main means to meet the 2 °C climate target can increase the wood prices drastically after 2030. The competitive position of the European forest industry is rather unaffected by use of wood for energy including biofuels.